PENGARUH KEMAMPUAN PENGELOLAAN KELAS OLEH GURU DENGAN MOTIVASI BELAJAR SISWA (Studi Korelasi di Sekolah Menengah Pertama Islam Terpadu Islamic Centre Bin Baz Kecamatan Ketungau Hilir Tahun Pelajaran 2019/2020) - Junaidi Junaidi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This research is motivated by the low motivation of student learning in the learning process, so it indirectly influences the cognitive learning outcomes of students. The purpose of this study was to determine the effect of class management ability on student motivation. The subjects in this study were all students Integrated Islamic Junior High School Bin Baz Islamic Center, Ketungau Hilir District totaling 60 students. Based on the results of simple regression analysis and hypothesis testing obtained a significant value of 0.002, the value is smaller than the α value of 0.05, this proves that there is a significant influence between the ability of classroom management on student motivation.